2012
DOI: 10.1364/josab.29.003027
|View full text |Cite
|
Sign up to set email alerts
|

Realizing self-similar pulses in solid-state laser systems

Abstract: A novel path to achieving self-similar pulses in an all-normal-dispersion solid-state laser resonator is presented and numerically examined. The spatially asymptotic self-similar solution to the nonlinear Schrödinger equation with gain is approached over many cavity round trips and the resultant steady-state solution, stabilized with a saturable absorber possessing a nearly rectangular power response profile, displays minimal spectral, temporal, and amplitude breathing. This method simplifies cavity constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Consequently, the optimal chirp introduced by the compressor was equal to 27 500 fs 2 ; after we increased the net cavity GDD by only 250 fs 2 (GDD = 110 fs 2 ), it approached 100 000 fs 2 . This, together with the purely linear chirp of the emitted radiation and a parabolicshaped spectrum could indicate that for GDD = −360 fs 2 the laser did not operate in a pure CPO regime and may have evolved toward a self-similar regime [22,23]. Mode-locking was self-starting in all of the described cases, with the threshold pump power being increased with the growth of positive dispersion.…”
Section: Cpo Regimementioning
confidence: 89%
“…Consequently, the optimal chirp introduced by the compressor was equal to 27 500 fs 2 ; after we increased the net cavity GDD by only 250 fs 2 (GDD = 110 fs 2 ), it approached 100 000 fs 2 . This, together with the purely linear chirp of the emitted radiation and a parabolicshaped spectrum could indicate that for GDD = −360 fs 2 the laser did not operate in a pure CPO regime and may have evolved toward a self-similar regime [22,23]. Mode-locking was self-starting in all of the described cases, with the threshold pump power being increased with the growth of positive dispersion.…”
Section: Cpo Regimementioning
confidence: 89%
“…Both passive and active self-similar pulses have been considered in the context of solid-state systems [49, 50]. Ilday et al found that even though the possible dispersion and nonlinearity of the solid-state format are considerably smaller than fiber, when a typical Ti:sapphire cavity was adjusted for large energy and net normal dispersion, weakly periodically-breathing passive self-similar behavior could be observed [49].…”
Section: Other Self-similar Lasersmentioning
confidence: 99%
“…Ilday et al found that even though the possible dispersion and nonlinearity of the solid-state format are considerably smaller than fiber, when a typical Ti:sapphire cavity was adjusted for large energy and net normal dispersion, weakly periodically-breathing passive self-similar behavior could be observed [49]. In contrast, Bucklew et al considered a laser with a static (no breathing) steady state evolution, consistent with the low nonlinearity, dispersion and gain per round trip [50]. They nonetheless showed this to be a novel kind of similariton laser wherein the similariton attractor is manifested over many round-trips as the laser modes lock.…”
Section: Other Self-similar Lasersmentioning
confidence: 99%